Exploring response surface of cutting forces for an end milling cutter - Kovač, Pavel (Journal of Production Engineering, 1984)
This paper deals with the fundamental determination of cutting forces in face milling, describes the measure equipment and computer use Some results including the variation of cutting forces with feed, speed and depth of cut are presented.